It's in You: Structural Sin and Personal Responsibility Revisited. (August 2021) - Hamilton, Brian
The language of structural sin is most often used to describe sin that inheres in laws, institutions, or social roles—in short, in the objective social architecture of our everyday lives. This article argues that structural sin should also be understood as including a subjective dimension, describing the determinate habits or dispositions instilled by sharing in the life of a particular society. Part of what is structured by structural sin, in other words, is agency itself. The reason that many theologians have resisted this idea is that it seems to undermine the conditions of moral responsibility. If our capacities for knowing and loving the good are always already concretely misshapen, can we rightly be held accountable for what we do? This article argues further that we can, drawing on the work of Judith Butler to sketch a fresh account of personal responsibility in the face of structural sin.